Children's participation in Dutch youth care practice: an exploratory study into the opportunities for child participation in youth care from professionals' perspective. Issue 1 (2nd January 2019) - Rap, Stephanie; Verkroost, Denise; Bruning, Mariëlle
ABSTRACT: Since 2015, local municipalities in the Netherlands have been responsible for the organisation of the youth care and child protection system. One of the basic assumptions underlying the new Youth Act (2015) is the mobilisation and empowerment of the family to help solve their problems. Consequently, the participation of children and parents is essential in the implementation of youth care services. However, it seems that substantial differences exist between municipalities in realising children's participation in decisions that are taken concerning their care and protection. This article provides an interdisciplinary perspective on child participation; it explores both the legal opportunities for participation and the extent to which children can make use of these opportunities in practice. It is concluded that municipalities have large discretion in giving shape to child participation in the access to voluntary and coercive youth care. However, child participation is better regulated and implemented in practice with respect to compulsory youth care via court orders. Throughout almost the entire process, the minimum age limit from when children are involved in the decision-making process is 12 years, which means that children below that age have scarce opportunities to participate.